2016
DOI: 10.1363/48e7216
|View full text |Cite
|
Sign up to set email alerts
|

Privacy and Confidentiality Practices In Adolescent Family Planning Care At Federally Qualified Health Centers

Abstract: The organizational practices used to ensure adolescent family planning confidentiality in FQHCs are varied across organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Best practices for supporting adolescents’ confidentiality when seeking SRH services have been established [ 26 , 27 ]; nevertheless, complex and contradictory policies regarding adolescents’ right to confidential care may continue to be a barrier to implementing safeguards to confidential care in some settings [ 28 ]. In this study we found that Medicaid-covered youth were less likely to report confidentiality concerns, suggesting the importance of programs that explicitly guarantee confidential care for adolescent access to SRH care.…”
Section: Discussionmentioning
confidence: 99%
“…Best practices for supporting adolescents’ confidentiality when seeking SRH services have been established [ 26 , 27 ]; nevertheless, complex and contradictory policies regarding adolescents’ right to confidential care may continue to be a barrier to implementing safeguards to confidential care in some settings [ 28 ]. In this study we found that Medicaid-covered youth were less likely to report confidentiality concerns, suggesting the importance of programs that explicitly guarantee confidential care for adolescent access to SRH care.…”
Section: Discussionmentioning
confidence: 99%
“…Family planning services are limited by governmental programs through commercial retail sales and are trying to adopt inappropriate aspects of family planning [ 15 ]. The aim of these centers should be to provide services to all, irrespective of the country’s economic situation, providing birth control methods using the medical profession and health services to adolescents to understand contraceptive options and to act quickly by choosing the most appropriate method [ 16 , 17 ]. There are many methods of contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Contraceptive methods are divided in natural, hormonal, intrauterine, spermicide, barrier methods and male contraception. Physical methods include periodic abstinence and coitus interruptus [ 17 , 18 ]. Effective contraceptive behaviors are not an individual achievement; on the contrary, choosing the right method depends on the increased resources that go into research and family planning services with reversible methods of contraception [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many family planning delivery sites face conflicts between state legal requirements for confidentiality of services and the level of confidentiality requested by patients. 32 Several recommendations to improve confidentiality of services are reported in a recent study on confidentiality and insurance billing at specialized family planning clinics. 33 This study recommends that providers screen for confidentiality at each appointment by asking questions such as: "Can we send a bill home that would say what services you got today?"…”
Section: Framework For Patient-centered Family Planning Servicesmentioning
confidence: 99%